GRAMMATICAL ERRORS IN THE USE OF VERB TENSES BY POLYTECHNIC STUDENTS AND METHODS FOR THEIR CORRECTION - Jonmaxmatova Maftuna Salohiddin qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION: This thesis examines the common errors in the use of verb tenses by polytechnic students and proposes effective methods for their correction. The study identifies the most frequent mistakes in Present Simple, Present Continuous, Past Simple, Present Perfect, and Future tenses. Causes of errors include interference from the native language, insufficient communicative practice, and learning grammar rules out  of  context.  The  thesis  highlights  the  importance  of  using  contextual  teaching, communicative exercises, error analysis, and digital technologies to improve students’ grammar competence. The implementation of these methods enhances students’ oral and  written  skills,  increases  their  communicative  activity,  and  prepares  them  for professional use of English.